Representasi Multikultural dalam Pertunjukkan Musik Dangdut Koplo - Muhammad Kamaluddin (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2018)
This research describes the matters of multicultural representation indangdut koplo. Multicultural colors are symbolically represented bysongs sung by their singers. The songs are sung with the rhythm ofmusical instruments that accompany the show. The description of thesymbolic representation is done by entering some song data into thesemiotic analysis model. From the multiple analysis of semioticanalysis, the idea of cultural semiotics is the main reference. Theresearch methodology used is descriptive qualitative traditionapproach. This is done to get the data in the form of song lyrics indangdut koplo show with the method refer to note. Data is obtainedfrom online impressions of youtube.com pages. From here it is knownthat the elements of multicultural enter in arbitrary into musicalperformances dangdut koplo. Of the existing, cultural diversity in thisgenre of music is represented by songs that speak Javanese,Sundanese, Indonesian, Arabic, Indian, English, and even Latin as asymbol.